A Study on the Performance of Co-Operative Banks in India and Their Contribution towards Financial Inclusion: Challenges and Opportunities for Co-operative Banks in Achieving Financial Inclusion (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The lack of access to financial services is a major roadblock towards economic development. India has the largest unbanked population and nearly 65 of adults across the country are excluded from the formal financial system. The onus of promoting financial inclusion rests on the government and financial institutions. Co-operative banks are low risk banks that were established to ensure rural credit, particularly to the farming sector, and thereby stabilize the wider banking system and facilitate economic development. India has the largest network of co-operative credit societies. The objective of the present study was to evaluate the performance of co-operative banks and assess their contribution in achieving financial inclusion in India. Operational and financial parameters like number of branches, population per branch, loans and advances, non-performing assets, credit flow to agriculture and net interest margin were considered for evaluation. The study found that even though there has been a significant increase in the number of branches, the distribution of these branches has been poorly strategized as indicated by the population covered by each branch. There are fewer number of branches in densely populated states which indicates the failure of the co-operative banks in promoting financial inclusion. Moreover, the growth of co-operative banks by numbers is not reflected in its share in credit flow to agriculture. The increase in total non-performing assets also indicates the mismanagement within the co-operative banks resulting in bad loans and low recovery. The findings of the study clearly indicate that the co-operative banks are unable to perform efficiently, profitably and promote financial inclusion.